2018
DOI: 10.3201/eid2411.180769
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Tuberculosis and Multidrug-Resistant Tuberculosis, Mbuji-Mayi Central Prison, Democratic Republic of the Congo

Abstract: After an alert regarding ≈31 tuberculosis (TB) cases, 3 of which were rifampin-resistant TB cases, in Mbuji-Mayi Central Prison, Democratic Republic of the Congo, we conducted an outbreak investigation in January 2015. We analyzed sputum of presumptive TB patients by using the Xpert MTB/RIF assay. We also assessed the Mycobacterium tuberculosis isolates’ drug-susceptibility patterns and risk factors for TB infection. Among a prison population of 918 inmates, 29 TB case-patients were already undergoing treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 25 publications
0
12
2
2
Order By: Relevance
“…The TB prevalence found by our study was threefold compared with the national estimate, and it was in line with the prevalence reported by an earlier assessment [ 7 ]. However, it was considerably lower than the rate reported by a study in DRC and was at the lower end of the prevalence reported by a review of studies published from 24 sub-Saharan African countries [ 11 ]. This review reported an HIV prevalence of 2%-35% among inmates with TB, and the prevalence we found was considerably higher (64%).…”
Section: Discussioncontrasting
confidence: 56%
“…The TB prevalence found by our study was threefold compared with the national estimate, and it was in line with the prevalence reported by an earlier assessment [ 7 ]. However, it was considerably lower than the rate reported by a study in DRC and was at the lower end of the prevalence reported by a review of studies published from 24 sub-Saharan African countries [ 11 ]. This review reported an HIV prevalence of 2%-35% among inmates with TB, and the prevalence we found was considerably higher (64%).…”
Section: Discussioncontrasting
confidence: 56%
“…Species identification and drug susceptibility testing performed with Genotype MTBDRplus Active TB Henostroza et al, 2013 [ 46 ] Zambia Cross-sectional study Lusaka Central Prison 2011 Digital X-ray/sputum smear microscopy, LED fluorescence, Lowenstein-Jensen Medium) culture. Active TB Kalonji et al, 2016 [ 47 ] Democratic Republic of the Congo Cross-sectional study Mbuji-Mayi Central Prison 2015 Clinical examination and bacteriological tests Active TB Karamagi et al, 2018 [ 48 ] Uganda Cross-sectional study 16 central and farm prisons (Names not specified) 2017 Combined quality improvement with facility-led active case finding (QI-ACF) Active TB Kayomo et al, 2018 [ 49 ] Democratic Republic of the Congo Cross-sectional study Mbuji-Mayi Central Prison 2015 Xpert MTB/RIF assay Active TB Kwabla et al, 2015 [ 50 ] Ghana Cross-sectional study Ho Prison 2014 Sputum smear microscopy Active TB Maggard et al, 2015 [ 51 ] Zambia Cross-sectional study Lusaka Central Prison, Livingstone Central Prison, Kabwe Prison Complex, 2011 Fluorescence microscopy, cultures, X-rays and physical examinations. Active TB Merid et al, 2018 [ 52 ] Ethiopia Cross-sectional study Hawassa prison 2016 Acid-fast bacilli, smear microscopy and molecular diagnostic testing (Xpert® MTB/RIF) Active TB Noeske et al, 2006 [ 53 ] Cameroon Cross-sectional study New Bell Central Prison of Douala 2004 Smear microscopy and/or culture Active TB Owokuhaisa et al, 2014 [ …”
Section: Resultsmentioning
confidence: 99%
“…All 31 articles scored between 57 and 86%. The majority (45.2%) of the included articles scored 71.4% (14/31) [ 36 , 39 , 40 , 42 , 45 , 46 , 49 , 50 , 53 56 , 60 , 61 ] and 10 (32.2%) scored 57.1% [ 35 , 37 , 38 , 41 , 43 , 44 , 47 , 48 , 52 , 57 ]. The remaining seven included articles scored the highest (85.7%) [ 32 34 , 51 , 58 , 59 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…With the increase in crowded high-rise office buildings using central air-conditioning, TB outbreaks in these settings will likely become more frequent. Although many TB outbreaks have been described in schools, prisons, homeless shelters and long-term care facilities [9][10][11][12], there have been very few reports of outbreaks in office buildings [5]. To illustrate how these outbreaks are handled and the problems involved, this report describes the interventions, investigations and results in a representative TB outbreak in an office building located in the centre of the HE region of Nanshan.…”
Section: Introductionmentioning
confidence: 99%